2011
DOI: 10.1016/j.toxicon.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of conotoxin types from Conus californicus reflects a diversity of prey types and a novel evolutionary history

Abstract: Most species within the genus Conus are considered to be specialists in their consumption of prey, typically feeding on molluscs, vermiform invertebrates or fish, and employ peptide toxins to immobilize prey. Conus californicus Hinds 1844 atypically utilizes a wide range of food sources from all three groups. Using DNA- and protein-based methods, we analyzed the molecular diversity of C. californicus toxins and detected a correspondingly large number of conotoxin types. We identified cDNAs corresponding to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Two conopeptides showing 41–44% sequence identity to the signal region of V-superfamily were classified as V-like group. These conopeptides contained cysteine patterns VI/VII (C-C-CC-C-C) (Olivera et al 1984) and XXII (C-C-C-C-C-C-C-C) (Elliger et al 2011). Also, two sequences showing similarity at the mature region to the conopeptide recently classified as Y2 superfamily (Lavergne et al 2013) were also identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two conopeptides showing 41–44% sequence identity to the signal region of V-superfamily were classified as V-like group. These conopeptides contained cysteine patterns VI/VII (C-C-CC-C-C) (Olivera et al 1984) and XXII (C-C-C-C-C-C-C-C) (Elliger et al 2011). Also, two sequences showing similarity at the mature region to the conopeptide recently classified as Y2 superfamily (Lavergne et al 2013) were also identified.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the generalist feeding behaviour of C. californicus has promoted the expression of extremely diverse conopeptides in this species that could not be classified according to the typical established gene superfamilies (Elliger et al 2011), while the specialized diet of Conus leopardus has significantly decreased the diversity of the expressed conopeptides (Remigio and Duda 2008). Therefore, the presence of diverse conopeptides in the venom duct of C. tribblei may reflect its wide range of prey preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, with the identification of RsXXIVA, only seven different peptides with four disulfide bonds have been reported [25,26,27,28,29,30]. The most extensively studied four disulfide bond conotoxin group is the I-superfamily group [31].…”
Section: Discussionmentioning
confidence: 99%
“…They selectively interact with Na + channels, presynaptic Ca 2+ channels or G protein-coupled presynaptic receptors in general [4,5]. However, we isolated a T-superfamily conotoxin TxVC (KPCCSIHDNSCCGL-NH 2 ) from C. textile years ago, determined its peptide sequence by Edman method [6], investigated its disulfide bond configuration using the synthesized peptide, and then surprisingly found that this TxVC selectively interacted with neuronal nicotinic acetylcholine receptor (nAChR) subtype a4b2 and a3b2 without obvious pharmacological effects on voltage-gated K + , Na + and Ca 2+ ion channels in DRG cells.…”
Section: Introductionmentioning
confidence: 99%